An improved two‐dimensional (2,4) finite‐difference time‐domain method for Lorentz dispersive media - Zygiridis, Theodoros T.; Amanatiadis, Stamatios A.; Kantartzis, Nikolaos V. (International journal of numerical modelling, 2024)
The credible solution of discretized Maxwell's equations in spaces occupied by Lorentz dispersive media is the main subject of this work. Specifically, we introduce a finite‐difference time‐domain (FDTD) algorithm with a typical (2,4) structure that features dispersion‐relation‐preserving characteristics and produces reduced numerical errors in two‐dimensional electromagnetic simulations, compared to the standard approach with similar computational requirements. We consider the case of dispersive media with non‐vanishing absorption coefficients and investigate different options for the suitable modification of the spatial approximations, so that the accomplished accuracy is optimized for a given computational overhead. The properties of the proposed FDTD technique are thoroughly examined, both theoretically and in numerical tests, and the performance upgrade compared with the conventional solution is assessed.